PENINGKATAN EFEKTIVITAS INSTITUSI PENDIDIKAN DAN PELATIHAN MELALUI KOMPETENSI PENGELOLA DAN PENYELENGGARA PENDIDIKAN DAN PELATIHAN - Eris Yustiono (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Sending employees to education and training programs has become the most common choice among institutions in order to improve their comptencies. It is believed that this approach is effective for improving employees’ specific capabilities for certain jobs. However, many factors may influence the accomplishment of the education and training programs, such as the eduaction and training organizers’ competency. Their competency determines how well the training proceeds as planned. Therefore, competency mastery for education and training organizers is definitely a necessity to be fulfilled.